Regularity of a boundary point for singular parabolic equations with measurable coefficients - Skrypnik, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We investigate the continuity of solutions of quasilinear parabolic equations near the nonsmooth boundary of a cylindrical domain. We prove a sufficient condition for the regularity of a boundary point, which coincides with the Wiener condition for the Laplace p-operator. The model case of the equations considered is the equation \(u t - Δ _p u = 0\) with the Laplace p-operator Δ p for 2n / (n + 1) < p < 2.